2017
DOI: 10.1073/pnas.1612833114
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the population-level impact of vaccines using synthetic controls

Abstract: When a new vaccine is introduced, it is critical to monitor trends in disease rates to ensure that the vaccine is effective and to quantify its impact. However, estimates from observational studies can be confounded by unrelated changes in healthcare utilization, changes in the underlying health of the population, or changes in reporting. Other diseases are often used to detect and adjust for these changes, but choosing an appropriate control disease a priori is a major challenge. The “synthetic controls” (cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 32 publications
4
92
1
Order By: Relevance
“…Reductions in AC‐CAP hospitalizations of 36%, 20% and 16% in children <2, 2–4 and 5–17 years of age, respectively, and even more pronounced decreases in PL‐CAP, are consistent with reports from most other countries . These findings are concordant with previous publications from Sweden that reported up to 37% reduction of inpatient all‐cause pneumonia in children < 2 years in 2012 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reductions in AC‐CAP hospitalizations of 36%, 20% and 16% in children <2, 2–4 and 5–17 years of age, respectively, and even more pronounced decreases in PL‐CAP, are consistent with reports from most other countries . These findings are concordant with previous publications from Sweden that reported up to 37% reduction of inpatient all‐cause pneumonia in children < 2 years in 2012 .…”
Section: Discussionsupporting
confidence: 92%
“…The first reports on reduced incidence of AC-CAP hospitalizations came from the United States, and thereafter from Canada and Finland [11,12,15]. However, in a recent study that adjusted for secular trends using the synthetic control method, there was no observed reduction of hospitalization for all-cause pneumonia after PCV-CIP introduction in any of five countries in the Americas (the United States, Mexico, Ecuador, Brazil and Chile) [9]. Neither was there a reduction in pneumonia among the elderly in Australia, and studies from the UK and Denmark have observed similar increases of AC-CAP in the elderly as in our study [13,14,16,27,28].…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison groups were a combination of multiple sets of diseases, having as a basis the ICD-10 codes groups proposed by Bruhn et al . [ 26 ], but performing a manual selection of which ones should be excluded from each age-groups. Excluded disease groups were those potentially influenced by the introduction of PCV-10 vaccine, those whose trend in the pre-vaccination period differed much from the observed trend for pneumonia, those that could have suffered the concurrent effect of another national public health intervention and those that were related to very short-stay or very long-stay hospitalizations.…”
Section: Methodsmentioning
confidence: 99%
“…As a demonstration of the point-and-click interface, we use hospitalization data from Chile among children <24 months (raw data available from http://www.deis.cl/) 5 Figure 5B). This yields 54% power to detect a rate ratio of 0.8 ( Figure 5B).…”
Section: Demonstration Of the Interfacementioning
confidence: 99%